2020
DOI: 10.1080/02508281.2020.1841374
|View full text |Cite
|
Sign up to set email alerts
|

Hunger for learning or tasting? An exploratory study of food tourist motivations visiting food museum restaurants

Abstract: This study investigates an underexplored area of research: the motivations of food tourists to visit a food museum and its respective restaurants as an emerging food tourism attraction. Using qualitative in-depth interviews with domestic Chinese food tourists at the Hangzhou Cuisine Museum and its restaurants, the findings suggest that their motivations are revealed at the individual, social, and institutional level resulting from behaviour displayed during the actual visit. At the individual level, the most d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 71 publications
(158 reference statements)
1
31
0
1
Order By: Relevance
“…The current research discovered that the inner needs of exploring and learning about the local coffee culture drove coffee tourists to an attraction, and they were the foundation of meaningful tourism experiences, which can be recalled in the future. Previous studies in the various contexts of food tourism have also identified the motivation for education and knowledge, such as seeking self-development experiences, is the foodies' main purpose for travelling (Mak et al, 2017;Moscardo et al, 2015;Park et al, 2020). However, Park et al (2020) pointed out that because domestic tourists' knowledge of their culturally and socially owned foods are not same as those of international, they may have more complex and deeper motivations for obtaining authentic experiences.…”
Section: Discussion and Implications Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current research discovered that the inner needs of exploring and learning about the local coffee culture drove coffee tourists to an attraction, and they were the foundation of meaningful tourism experiences, which can be recalled in the future. Previous studies in the various contexts of food tourism have also identified the motivation for education and knowledge, such as seeking self-development experiences, is the foodies' main purpose for travelling (Mak et al, 2017;Moscardo et al, 2015;Park et al, 2020). However, Park et al (2020) pointed out that because domestic tourists' knowledge of their culturally and socially owned foods are not same as those of international, they may have more complex and deeper motivations for obtaining authentic experiences.…”
Section: Discussion and Implications Discussionmentioning
confidence: 99%
“…Previous studies in the various contexts of food tourism have also identified the motivation for education and knowledge, such as seeking self-development experiences, is the foodies' main purpose for travelling (Mak et al, 2017;Moscardo et al, 2015;Park et al, 2020). However, Park et al (2020) pointed out that because domestic tourists' knowledge of their culturally and socially owned foods are not same as those of international, they may have more complex and deeper motivations for obtaining authentic experiences. Thus, further research can be conducted to clarify the differences of coffee tourism motivations between domestic and international tourists.…”
Section: Discussion and Implications Discussionmentioning
confidence: 99%
“…Several new motivations have been identified that attract tourists to pursue travel (Chen & Zhou, 2021; Dann, 1981; Gnoth, 1997). ‘Experiencing authentic food’ has been one of the new tourist motivators (Park et al, 2020; Rousta & Jamshidi, 2019). Food tourism (FT) is described as a visit to a place to experience authentic local food (World Food Travel Association, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The pursuit and enjoyment of unique and memorable food and beverage experiences for both far and near is known as food tourism (World Food Travel Association, 2021). Previous researchers proved that food and tourism were a complement to each other which generate continuous intense research interest (Atikahambar et al, 2018;Chi et al, 2013;Fauntain, 2021;Jalis et al, 2009;Karim et al, 2010;Park et al, 2020;Rousta & Jamshidi, 2019;Yeap et al, 2019). Since food has been a major attraction for visitors, many destinations have tried to give tourists unique culinary experiences (Cohen & Avieli, 2004;Tsai & Wang, 2017).…”
Section: Introductionmentioning
confidence: 99%